2021
DOI: 10.1021/acs.inorgchem.0c03614
|View full text |Cite
|
Sign up to set email alerts
|

A Bis (BICAAC) Palladium(II) Complex: Synthesis and Implementation as Catalyst in Heck-Mizoroki and Suzuki-Miyaura Cross Coupling Reactions

Abstract: Carbenes are one of the most appealing, well-explored, and exciting ligands in modern chemistry due to their tunable stereoelectronic properties and a wide area of applications. A palladium complex (BICAAC)2PdCl2 with a recently discovered cyclic (alkyl)­(amino)­carbene having bicyclo[2.2.2] octane skeleton (BICAAC) was synthesized and characterized. The enhanced σ-donating and π-accepting ability of this carbene lend a hand to form a robust Pd-carbene bond, which allowed us to probe its reactivity as a precat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The modification of the ring allowed the synthesis of bicyclic carbenes (BICAAC‐6) with favorable electronic and steric properties (Scheme 2). [28] Although some transition metal complexes of BICAAC ligands have recently been reported, their ruthenium derivatives are rare [38–42] …”
Section: Methodsmentioning
confidence: 99%
“…The modification of the ring allowed the synthesis of bicyclic carbenes (BICAAC‐6) with favorable electronic and steric properties (Scheme 2). [28] Although some transition metal complexes of BICAAC ligands have recently been reported, their ruthenium derivatives are rare [38–42] …”
Section: Methodsmentioning
confidence: 99%
“…44c In 2021, Singh et al reported a (BICAAC) 2 PdCl 2 complex that showed better catalytic performance than other (NHC) 2 Pd catalysts for the Heck-Mizoroki and Suzuki-Miyaura cross-coupling reactions (Scheme 16). 45 Only a 0.5 mol% catalyst loading was sufficient for these reactions, whereas a 1-3 mol% catalyst loading was needed for other (NHC) 2 Pd catalysts.…”
Section: Bicaacmentioning
confidence: 99%
“…[9] Encouraged with the favourable ligand properties of BICAACs, we became interested to further harness the potential of metal-Me BICAAC complexes. Recently, we have reported on the catalytic activity of ( Me BICAAC) 2 PdCl 2 complex for Heck-Mizoroki and Suzuki-Miyaura cross-coupling reactions, [10] the reactivity of Me BICAAC with different hydroboranes [11] and synthesis of two coordinated Cu(I) and Au(I) complexes supported by Me BICAAC. [12] In the present report, we have synthesized Me BICAAC supported nickel complexes [( Me BICAAC) 2 NiX 2 ] (X = Cl (1), Br (2) and I (3)).…”
Section: Introductionmentioning
confidence: 99%